# Chapter 1 Exercise B

1. Solution: By definition, we have$(-v)+(-(-v))=0\quad\text{and}\quad v+(-v)=0.$This implies both $v$ and $-(-v)$ are additive inverses of $-v$, by the uniqueness of additive inverse, it follows that $-(-v)=v$.

2. Solution: If $a\ne 0$, then $a$ has inverse $a^{-1}$ such that $a^{-1}a=1$. Hence $v=1\cdot v=(a^{-1}a)v=a^{-1}(av)=a^{-1}\cdot 0=0.$Here we use associativity in 1.19 and and 1.30.

3. Solution: Let $x=\dfrac{1}{3}(w-v)$, then $v+3x=v+3\cdot \dfrac{1}{3}(w-v)=v+(w-v)=w.$This shows existence. Now we show uniqueness. Suppose, we have another vector $x’$ such that $v+3x’=w$. Then $v+3x’=w$ implies $3x’=w-v$. Similarly, $3x=w-v$. Hence $3(x-x’)=3x-3x’=(w-v)-(w-v)=0.$By Problem 2, it follows that $x-x’=0$. This shows uniqueness.

4. Solution: Additive identity: there exists an element $0\in V$ such that $v+0=v$ for all $v\in V$ ; This means $V$ cannot be empty.

5. Solution: If we assume the additive inverse condition, we already showed $0v=0$ for all $v\in V$ in 1.29. Now we assume $0v=0$ for all $v\in V$ and then show additive inverse condition. Since we have $0v=0$ for all $v\in V$, we have $v+((-1)v)=1v+((-1)v)=(1+(-1))v=0v=0,$this means the existence of additive inverse, i.e. the additive inverse condition.

6. Solution: This is not a vector space over $\mathbb R$. Consider the distributive properties in 1.19. If this is a vector space over $\mathbb R$, we will have $\infty=(2+(-1))\infty=2\infty+(-1)\infty=\infty+(-\infty)=0.$Hence for any $t\in\mathbb R$, one has$t=0+t=\infty+t=\infty=0.$We get a contradiction since zero vector is unique.